SOX2 expression in the primary tumor of castration-naive metastatic prostate adenocarcinoma in association with metastasis extent - Saraswati, Meilania; Kekalih, Aria; Lisnawati; Rahadiani, Nur; Asmarinah; Hernowo, Bethy Suryawathy; Hamid, Agus Rizal Ardy Hariandy; Mochtar, Chaidir Arif (Medical Journal of Indonesia, 2026)
BACKGROUND Poor prognosis in patients with metastatic prostate adenocarcinoma (mPCa) may be due to the expression of stem cell-related genes. This study aimed to demonstrate the association between the expression of cancer stem cell markers and metastasis in patients with castration-naive mPCa. METHODS This cross-sectional, analytical study investigated a formalin-fixed paraffin-embedded prostate specimens from patients diagnosed in Cipto Mangunkusumo Hospital. Patients aged ≥50 years old were grouped based on the extent of metastases (high-volume disease [HVD] and low-volume disease [LVD]). In each case, immunohistochemical staining for CD133, CD44, SOX2, and androgen receptor was performed and analyzed using H-score. All data were recorded and analyzed using SPSS software version 20.0. RESULTS A total of 61 patients were recruited from 2020 to 2023 and divided into the HVD (n = 38) and LVD (n = 23) groups, with a mean age of 67.9 years. 45 of the patients had International Society of Urological Pathology (ISUP) grade 5 disease, while 16 of them had grade <5. A significant difference of ISUP grade and PSA serum level was observed in the HVD versus LVD group (p = 0.017 and <0.001, respectively). Additionally, a significant association was found between SOX2 expression and metastatic extent. CONCLUSIONS The LVD group showed higher SOX2 expression in the primary tumor compared to the HVD group. Different SOX2 expressions in various sites and stages may be due to the cancer cells’ systemic network.